Acute appendicitis: Analysis of 518 histopathologically diagnosed cases at the Kathmandu University Hospital, Nepal - Makaju, R; Mohammad, A; Shakya, A (Kathmandu University Medical Journal, 2010)
Background: Appendicitis is important as it is a common surgical emergency. There is no medical treatment for it, timely surgery is mandatory to prevent morbidity and mortality. Objectives: The objective of this study was to analyse the pathologic findings, the demographics, and, look for the existence of the so called aetiopathogenetic factors in the context of current prevailing beliefs regarding acute appendicitis, the most common current reason for emergency abdominal surgery. Materials and methods: This was a retrospective study. It was carried out at the Kathmandu University Hospital, Dhulikhel, Kavre, Nepal. All histopathologically diagnosed cases of acute appendicitis during the period January 1, 2004 to April 30, 2010 were included. Their macrospcopic and light microscopic examination findings were analyzed. Results: A total of 518 histopathologically diagnosed cases of acute appendicitis were found. Age distribution of these cases was between 6 to 84 years. Mean age was 30. 94 ± 15.75 years. Sex distribution consisted of 313 (60.42%) cases in males and 205 (39.58%) cases in females. Fecalith in the appendiceal lumen was seen only in 8 (1.54%) of cases. Granuloma and carcinoid was seen in 3 (0.58%) and 1 (0.19%) cases respectively. Perforation was seen in 11 (2.12%) cases. Foreign bodies, gallstones, strictures, helminthic infection, carcinoma or any other obvious/apparent aetiologic/ pathogenetic lesions/findings were not seen in any of the cases. Histopathologically staged distribution revealed that 180 (34.75%) cases were of early acute appendicitis, 250 (48.26%) cases were of acute suppurative appendicitis, and 88 (16.99%) cases were of acute gangrenous appendicitis. Conclusion: This study did not confirm the existing popular notion that luminal obstruction is the pathogenetic hallmark for acute appendicitis. Therefore, further research on this common surgical emergency is surely warranted. Key words: Acute appendicitis; fecalith; gangrenous DOI: 10.3126/kumj.v8i2.3564 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 227-230